1999
DOI: 10.1177/0265407599164001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Projection and Empathic Accuracy in Dyadic Perception between Older Twins

Abstract: Dyadic perception between 108 older identical and same-sex fraternal twin pairs was examined using three different tasks: (i) an emotional sensitivity task, (ii) a Q-Sort rating of emotion-eliciting situations, and (iii) an assessment of each other's personality traits. Idiographic analyses related judgements of self and co-twin within and between twins. Projection approached the reliability of the judgements and was significantly higher than both empathic accuracy and actual similarity, suggesting that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
(69 reference statements)
2
32
0
Order By: Relevance
“…In line with the literature (Hoch, 1987;Kenny and Acitelli, 2001;Neyer et al, 1999;Thomas et al, 1997) we expected higher coefficients for assumed similarity than for accuracy (H-2). We found some evidence for H-2, but our results suggest that gender, the type of situation and the particular feelings being judged need also to be taken into account.…”
Section: Assumed Similarity In Judging the Absent Partner's Feelingssupporting
confidence: 89%
See 3 more Smart Citations
“…In line with the literature (Hoch, 1987;Kenny and Acitelli, 2001;Neyer et al, 1999;Thomas et al, 1997) we expected higher coefficients for assumed similarity than for accuracy (H-2). We found some evidence for H-2, but our results suggest that gender, the type of situation and the particular feelings being judged need also to be taken into account.…”
Section: Assumed Similarity In Judging the Absent Partner's Feelingssupporting
confidence: 89%
“…There is empirical evidence that it is a common strategy to use one's own experience as an anchor to judge other persons' experiences (Markus et al, 1985;Nickerson, 1999). Various studies have demonstrated strong assumed similarity or projection that was higher than accuracy in most of the cases (Hoch, 1987;Kenny and Acitelli, 2001;Neyer et al, 1999;Thomas et al, 1997). Thus, we expect this also to be true in our study: When spouses judge their absent partner's feelings, assumed similarity will be higher than accuracy (Hypothesis H-2).…”
Section: Where Might Accuracy In Judging An Absent Partner's Feelingsmentioning
confidence: 52%
See 2 more Smart Citations
“…However, we hope that future work will port this approach to the study of other processes, such as stereotyping and projection (Hoch, 1987;Judd & Park, 1993;Jussim, 1991;Neyer, Banse, & Asendorpf, 1999); other forms of accuracy, such as predictions of one's own future experiences Kermer, Driver-Linn, Wilson, & Gilbert, 2006;Wilson, Wheatley, Meyers, Gilbert, & Axsom, 2000); and other forms of adaptive behavior, such as successful negotiation, cooperation, and accurate prediction about others' actions (Coricelli & Nagel, 2009;Galinsky, Maddux, Gilin, & White, 2008;Hampton, Bossaerts, & O'Doherty, 2008;Valdesolo, Ouyang, & DeSteno, 2010). However, we hope that future work will port this approach to the study of other processes, such as stereotyping and projection (Hoch, 1987;Judd & Park, 1993;Jussim, 1991;Neyer, Banse, & Asendorpf, 1999); other forms of accuracy, such as predictions of one's own future experiences Kermer, Driver-Linn, Wilson, & Gilbert, 2006;Wilson, Wheatley, Meyers, Gilbert, & Axsom, 2000); and other forms of adaptive behavior, such as successful negotiation, cooperation, and accurate prediction about others' actions (Coricelli & Nagel, 2009;Galinsky, Maddux, Gilin, & White, 2008;Hampton, Bossaerts, & O'Doherty, 2008;Valdesolo, Ouyang, & DeSteno, 2010).…”
Section: Discussionmentioning
confidence: 99%